Judicial Activism and Constitutional Boundaries: A Normative Study of Constitutional Court Decision-Making in Indonesia - Mardana Rifta Oktaviana; Achmad Hidayatullah (Lex Recta: Journal of Law and Normative Justice, 2026)
This research examines the constitutional boundaries of judicial activism in the decision-making practice of the Indonesian Constitutional Court through a normative–doctrinal approach. Grounded in the 1945 Constitution, Law No. 24 of 2003 as amended by Law No. 7 of 2020, and Law No. 12 of 2011, the study analyzes doctrinal patterns such as conditional constitutionality, ultra petita reasoning, and open legal policy intervention. By employing systematic, teleological, and structural interpretation, the article constructs a cumulative normative boundary test based on textual fidelity, structural coherence, rights necessity, institutional prudence, and doctrinal consistency. The findings indicate that judicial activism becomes constitutionally legitimate only when interpretative expansion remains demonstrably anchored in constitutional mandates and proportionate remedial design. Conversely, boundary diffusion arises when remedial innovation effectively substitutes legislative policy choices without clear constitutional compulsion. The study contributes theoretically by reframing judicial activism as a conditional constitutional function rather than an inherent judicial disposition, and methodologically by integrating doctrinal mapping with structured evaluative criteria. The proposed framework offers a principled guide for assessing constitutional adjudication legitimacy in transitional democracies